Prevalence of Preeclampsia and Associated Factors among Antenatal Care Attending Mothers at Tirunesh Beijing General Hospital, Addis Ababa, Ethiopia - Esubalew Tesfahun; Selam Tadesse; Awraris Hailu; Abebe Minda; Meseret Ekubay; Behailu Tariku; Abinet Dagnaw (Hindawi Limited, 2023)
Background. Hypertensive condition during the pregnancy of the mother that usually occurs after 20 weeks of gestation age is clinically considered preeclampsia. This health problem of pregnant mothers can lead to various complications for both the mother and the baby. But the risk factors for preeclampsia have not been well documented. Therefore, availing up-to-date information on the prevalence and associated factors of preeclampsia is essential for its early identification and management. This study aimed to assess the prevalence of preeclampsia and associated factors among pregnant women attending antenatal care (ANC). Methods. Cross-sectional study design was used from March 1, 2022, to March 30, 2022, among 235 pregnant women attending antenatal care at Tirunesh Beijing General Hospital (TBGH) from March 1, 2022 March 30, 2022, in Addis Ababa, Ethiopia. Systematic random sampling was employed to get study participants from antenatal care attendants. Data were collected by an interviewer-administered questionnaire. The presence of statistical association was determined using an adjusted odds ratio (AOR) with a 95% confidence interval (CI). Variables with P values less than 0.05 were considered statically significant. Result. A total of 235 participants were enrolled in the study with a 99.1% response rate. The prevalence of preeclampsia among the current pregnant women who attended ANC in Tirunesh Beijing General Hospital was 5.5% with 95% CI (AOR = 1.3-10.0). Significant variables such as respondents age >35 years, 2.1 (AOR = 1.3-3.4), history of preeclampsia 8.5 (AOR = 1.2-10.3), history of hypertension 2.9 (AOR = 3.0-7.3), ANC visit <3 times 8.5 (AOR = 3.1-13.4), and family history of hypertension 2.2 (AOR = 1.24.3) were significantly associated with preeclampsia. Conclusion. A considerable proportion of pregnant women were experiencing preeclampsia. History of preeclampsia and hypertension, family history of hypertension, and maternal age were associated factors of preeclampsia. Therefore, health professionals working in health institutions give more attention to controlling hypertension during antenatal service.